Human capital and global business strategy - Thomas, Howard, 1943-; Smith, Richard R., 1962-; Diez, Fermin, 1960- (Cambridge : Cambridge University Press, 2013)
Human capital - the performance and the potential of people in an organisation - has become an increasingly urgent issue for business leaders. Dramatic demographic shifts, the globalisation of organisations, increasing business complexity, and generational differences are causing many organisations to place a more deliberate focus on human capital as a key element in strategic planning and execution. This book helps business leaders determine how to address human capital as part of their business strategy, to drive value and realise the potential of the organisation. Topics are presented clearly, allowing readers to quickly grasp and apply key concepts and ideas. The authors share both their academic research and practical experience from around the world, providing first-hand case studies and examples to help bring theoretical topics to life. With a strong practitioner focus, this book will provide business leaders and HR professionals with new insights into how to improve business performance through a unique, strategic approach to human capital.
Machine generated contents note: Foreword; 1. Introduction; 2. Culture; 3. Leadership; 4. Structure; 5. Talent management; 6. Human capital metrics; 7. Change management; 8. Conclusion; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Human capital; Strategic planning